Émile Benoit playing a character - Ryan, Sandra (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Report of a field trip to Mainland, Port-au-Port Peninsula, Newfoundland, March 10-14, 1990 » . -- Photo is one of a series associated with a Memorial University folklore student term paper: "Report of a field trip to Mainland, Port-au-Port Peninsula, Newfoundland, March 10-14, 1990".